EFFECTIVENESS OF GIBBERELLINS IN BREAKING DORMANCY OF SNAKEFRUIT SEEDS (SALACCA SNAKEFRUIT GEARTNER) - Enny Adelina; Nuraeni Nuraeni; Yohanis Tambing; Ida Musdalifa (AGROLAND The Agricultural Sciences Journal (e-Journal), 2020)
This study aims to examine the effectiveness of gibberellins in breaking dormancy to produce high viability snakefruit (Salacca snakefruit Geartner) seeds. The materials used are snakefruit seeds from Tamareja Village, Donggala Regency, sterile sand media, aquades, and GA3 solution. This research was arranged using a completely randomized design (CRD) with one factor, namely the provision of gibberellin, consisting of five levels of concentration, namely P0 = control (without treatment), P1 = 30 ppm and P2 = 40 ppm P3 = 50 ppm P4 = 60 ppm. each treatment was repeated five times so that there were 25 experimental units. Each experimental unit used 20 seeds. Observation data were analyzed using analysis of variance (ANOVA), followed by Tukey' HSD test if the treatment tested showed a significant effect. The results showed that gibberellin administration effectively broke snakefruit seeds' dormancy and produced seeds with high viability. The higher the gibberellins' concentration would increase germination speed plumule length, radicle length, and faster embryo axis emergence. Gibberellin 60 ppm resulted in germination power 98%, germination rate 20.97 days, plumule length 5.52 cm, radicle length 5.15 cm, and embryo axis emergence 9.2 days.